Definition of everyday aesthetics [Definición de estética cotidiana] (2017)
This article responds to recent controversy around the concept of of everyday aesthetics with a succinct definition aimed at clarifying the object of study. To enable the use and accessibility, the article intentionally resorts to brevity.